2(2t-3)=6(t-2)

Simple and best practice solution for 2(2t-3)=6(t-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2t-3)=6(t-2) equation:


Simplifying
2(2t + -3) = 6(t + -2)

Reorder the terms:
2(-3 + 2t) = 6(t + -2)
(-3 * 2 + 2t * 2) = 6(t + -2)
(-6 + 4t) = 6(t + -2)

Reorder the terms:
-6 + 4t = 6(-2 + t)
-6 + 4t = (-2 * 6 + t * 6)
-6 + 4t = (-12 + 6t)

Solving
-6 + 4t = -12 + 6t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-6t' to each side of the equation.
-6 + 4t + -6t = -12 + 6t + -6t

Combine like terms: 4t + -6t = -2t
-6 + -2t = -12 + 6t + -6t

Combine like terms: 6t + -6t = 0
-6 + -2t = -12 + 0
-6 + -2t = -12

Add '6' to each side of the equation.
-6 + 6 + -2t = -12 + 6

Combine like terms: -6 + 6 = 0
0 + -2t = -12 + 6
-2t = -12 + 6

Combine like terms: -12 + 6 = -6
-2t = -6

Divide each side by '-2'.
t = 3

Simplifying
t = 3

See similar equations:

| 57x+4334635x-30409234809x=28934237409x+23423423x*12312321x | | 7t-8=2+5t | | -2+p+2p+2=-12 | | 5m-12=-10+4m | | -36-b-4b=64 | | 5m+1=-23 | | 11.3-7.2=-3.82 | | 1.3-7.2=-3.82 | | 8.4s-s=14.8 | | -5z+3z-7=8z-1-6 | | 3x-2=4x-8 | | 7n^2-43n+6=0 | | n^2=n | | 7p^2-27p-40=0 | | 5a=20 | | -7=2y-3-3y | | 3x-7(-2x+8)=-5 | | 3x-7y=-5 | | 10n+8p=0 | | S=3t+40 | | (x-1)+(x+3)=2x | | k-8(7+k)=-1(5) | | 4t-3-3t=-5 | | 9x+3y=4 | | (3x+4)(2-5x)=0 | | c=(2)(3.14)(r) | | 9x-4y=-2 | | 6.3y=4.1y+12 | | 1.2=1.6m | | c=23 | | -8=5a-3a | | -54=133.578499968x+0.5*0.0209625668*17843.21565 |

Equations solver categories